Staff time requirements for postoperative pain management: Comparison of sufentanil sublingual tablet system and intravenous patient-controlled analgesia - Meuser, Thomas; Nardi-Hiebl, Stefan; Eberhart, Leopold; Paul, Matthias; Böttger, Robert; Reutershan, Jörg (Journal of Opioid Management, 2020)
Objective: Assessment and allocation of required staff time for postoperative pain management for two different patient-controlled technologies, sufentanil sublingual tablet system (SSTS) and intravenous analgesia (PCiA). Design: Activity-based evaluation. Setting: The study was conducted at four German hospitals based on the availability of the two technologies studied and their respective bed capacity broadly reflecting the German hospital landscape. Patients and participants: Staff activities were recorded for 162 SSTS and 154 PCiA procedures. Every hospital recorded around 40 procedures for each technology between December 2016 and July 2017. Interventions: Staff time was recorded if a patient received one of the two considered postoperative pain management technologies and was under treatment of a trained nurse. No further criteria were defined. Documentation of resource utilization covered all staff activities concerning the two technologies by detailed activity recording forms. Main outcome measure(s): Staff time for five identified process areas (preparation of therapy option, provisioning at patients' bed, therapy, removal of therapy option, reprocessing, and storage) with significant impact on the entire process. Results: The average staff time required for SSTS to manage the entire process was 36 minutes whereas for PCiA it was 49 minutes (p < 0.0001). In all process areas, SSTS showed significantly less staff time requirements. Conclusions: In comparison to PCiA, SSTS requires significantly less staff time to manage postoperative pain in the studied setting.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Activity-based evaluation; Staff time; Zalviso